Moderate feminism within or against the neoliberal university? The example of Athena SWAN. Issue 8 (13th January 2019) - Tzanakou, Charikleia; Pearce, Ruth
Abstract : This article argues that gender equality programmes in universities and colleges may operate as a form of 'moderate feminism', producing contradictions through simultaneously providing a site of resistance and complicity for feminists. Our argument draws on a critical and empirical analysis of the Athena SWAN (Scientific Women's Academic Network) charter mark, which originated in the UK. We argue that Athena SWAN is a product of neoliberalization within the UK's academic environments, reflecting the tendency towards accountability, metrics and the performative 'doing' of equality work within this context. We problematize the operationalization and implementation of Athena SWAN processes in departments and universities, describing contradictions and caveats. Athena SWAN can lead to benefits and (limited) achievements in terms of culture change and institutional initiatives. However, the burden of undertaking this work predominantly falls upon women and other marginalized groups, such as people of colour and lesbian, gay, bisexual and transgender (LGBT) people. Equality programmes such as Athena SWAN are often poorly designed to address complex issues, such as intersectional identities and discrimination experienced by self‐assessment team members. Nevertheless, we identify potential in utilizing Athena SWAN as a site of resistance and means to foster collective solidarity to work against neoliberal practices.